The bismuth oxyhalide family: thin film synthesis and periodic properties. Issue 35 (24th August 2018) - Gómez-Velázquez, Laura S.; Hernández-Gordillo, Agileo; Robinson, Matthew J.; Leppert, Valerie J.; Rodil, Sandra E.; Bizarro, Monserrat
Abstract : The complete bismuth oxyhalides were synthesized as thin films. β-Bi2 O3 films were transformed into BiOX for X = F, Cl and Br by chemical baths; BiOI was obtained by spraying the solution directly. All BiOX films present photocatalytic activity under simulated sunlight. Abstract : Bismuth oxyhalides (BiOX, where X = F, Cl, Br, I) are interesting materials due to their layered structure, which can be useful for different applications. In this work, we present the synthesis of the complete BiOX family in the thin film form. The tetragonal phase Bi2 O3 film deposited onto a glass substrate was transformed into BiOF, BiOCl or BiOBr by a simple immersion at ambient temperature in a halide (X = F, Cl, Br) containing solution. For these films, a residual phase from the oxide was present and for BiOF another phase (tentatively identified as Bi7 O5 F11 ) was present too. For the BiOI film synthesis, an iodine and bismuth containing solution was sprayed onto the glass substrate heated at 275 °C and a pure phase was obtained. Microstructural and morphological characterization was performed by X-ray diffraction and scanning electron microscopy, while the chemical environment was studied by X-ray photoelectron spectroscopy. Optical and photocatalytic properties were also obtained. The physical and chemical characteristics of the BiOX films follow a correlation with the atomic radius of the halogen atom incorporated into the corresponding lattice. All the BiOX films showed a photocatalytic response for the photodiscoloration of indigo carmine dye under simulated sunlight irradiation in an alkaline medium. The photocatalytic reactions occurred via 2 proton–electron transfer from the oxide or oxyhalide to the adsorbed IC dye, favoring its reduction to the corresponding leuco IC form.